Progressive loss of myogenic differentiation in leiomyosarcoma has prognostic value. Issue 5 (12th January 2015) - Demicco, Elizabeth G; Boland, Genevieve M; Brewer Savannah, Kari J; Lusby, Kristelle; Young, Eric D; Ingram, Davis; Watson, Kelsey L; Bailey, Marshall; Guo, Xiangqian; Hornick, Jason L; van de Rijn, Matt; Wang, Wei‐Lien; et al.
<x xml:space="preserve">Abstract</x> Aims Well‐differentiated leiomyosarcomas show morphologically recognizable smooth muscle differentiation, whereas poorly differentiated tumours may form a spectrum with a subset of undifferentiated pleomorphic sarcomas. The expression of certain muscle markers has been reported to have prognostic impact. We investigated the correlation between the morphological spectrum and the muscle marker expression profile of leiomyosarcoma, and the impact of these factors on patient outcomes. Methods and results Tissue microarrays including 202 non‐uterine and 181 uterine leiomyosarcomas with a spectrum of tumour morphologies were evaluated for expression of immunohistochemical markers of muscle differentiation. Poorly differentiated tumours frequently lost one or more conventional smooth muscle markers [smooth muscle actin, desmin, h‐caldesmon, and smooth muscle myosin (P < 0.0001)], as well as the more recently described markers SLMAP, MYLK, and ACTG2 (P < 0.0001). In primary tumours, both desmin and CFL2 expression predicted improved overall survival in multivariate analyses (P = 0.0111 and P = 0.043, respectively). Patients with muscle marker‐enriched tumours (expressing all four conventional markers or any three of ACTG2, CFL2, CASQ2, MYLK, and SLMAP) had improved overall survival (P < 0.05) in univariate analyses. Conclusions Morphologically and immunohistochemically, poorly differentiated leiomyosarcomas can masquerade as undifferentiated pleomorphic sarcomas with progressive loss of muscle markers. The expression of muscle markers has prognostic significance in primary leiomyosarcomas independently of tumour morphology.